BUILDING RELIGIOUS MODERATIONS THROUGH THE CYBER PEDAGOGY: A DIGITAL ETHNOGRAPHIC PERSPECTIVE (International Conference on Social and Islamic Studies, 2022)
Religious observance in Indonesia is a reality that is not separated from the context of Indonesian life. Religious equality became the hallmark of the Indonesian nation. When it comes to Indonesia, then its constraints are religious, tribal and racial. Such as diversity requires strategies, methods and instruments that match that context. One model developed in order to care for such stewardship is religious moderation. The focus of religious moderation is building harmony, balance and religious tolerance. The target of the religious moderation model is all citizens. From here on, religious moderations are presented to the digital penetration reality. Facing that reality, the study suggests an approach to building moderations in the digital era of the cyber pedagogy. The systematic emphasis on pedagogy isa digitized utilization as an instrument in building a religious and moderate spirit. The cyber pedagogy combines conventional models with digitisation models as instruments in building religious moderation literacy. This model is then given a weighted digital ethnographic perspective as a way of looking at developing a religious moderation model in the middle of digitalization penetration. Thus, religious and humanitarian dimensions that promote social relations, solidarity, and tolerance continue to be maintained as religious strengths realities of diversity.